ACCOUNTING: KIN TO THE HUMANITIES? - Cullather, James L. (The Accounting Review, 1959)
Abstract The article focuses on accounting as the kin to the humanities. Teachers of accounting are well aware of the patronizing glance. Usually they get it from the scholars in the Liberal Arts. Especially and amusingly, they get it from their friends in Economics. In present ponderings there is soul searching about the broadening character of business courses and their liberal content. Business educators probably never have felt that it was only in designated liberal areas that a business student received a liberal education. At any moment, the accounting teacher understands that his lecture is touching on law, economics, labor relations, public finance, and a host of other areas. The liberal leanings of the teacher, however, may be bound in the strait jacket of subject. But accounting is no strait jacket. On the contrary, it opens the way to liberal expanses. Attention is directed sharply to the temporary nature of earthly things by this accounting topic. Someone may take issue with the observation that accounting can lift the student to the world of ideas and pose for him/her issues of man in the universe.